Mirror‐Image Dependence: Targeting Enantiomeric G‐Quadruplex DNA Using Triplex Metallohelices. Issue 48 (2nd November 2018) - Zhao, Chuanqi; Song, Hualong; Scott, Peter; Zhao, Andong; Tateishi‐Karimata, Hisae; Sugimoto, Naoki; Ren, Jinsong; Qu, Xiaogang
Abstract: Naturald ‐DNA andl ‐DNA are mirror‐image counterparts. However, because of the inherent flexibility and conformation diversity of DNA, it is still not clear how enantiomeric compounds recognized ‐DNA andl ‐DNA. Herein, taking G‐quadruplex (G4) DNA as an example that has diverse conformations and distinct biofunctions, the binding of ten pairs of iron triplex metallohelices tod ‐ andl ‐G4 DNA were evaluated. The Δ‐enantiomer binds tod ‐DNA and the Λ‐enantiomer binds tol ‐DNA, exhibiting almost the same stabilization effect and binding affinity. The binding affinity of the Δ‐metallohelix withd ‐G4 is nearly 70‐fold higher than that of Λ‐metallohelix bindingd ‐G4. Δ‐Metallohelix binding tod ‐G4 follows a two‐step binding process driven by a favorable enthalpy contribution to compensate for the associated unfavorable entropy. Abstract : Mirror, mirror : Chiral recognition of DNA plays crucial roles in many DNA‐relevant events. The binding of ten pairs of iron helical metallohelices to enantiomeric G‐quadruplex DNA was screened. The results clearly show mirror‐image dependence for the Δ‐ and Λ‐enantiomers binding tod ‐ andl ‐DNA, respectively.